Credo Alteram, or the Problem with Some Augustan Centurions in Times of Peace - Faszcza, Norbert Michał (Polskie Towarzystwo Filologiczne, 2020)
The aim of my article is to explain the source of the problems with the Augustan centurions, which Tacitus described in the first book of the Annales. Through the analysis of the promotion system inherited from the Republican period, I have made an attempt to determine which characteristics might have helped a soldier to become a centurion. Tacitus mentioned a centurion named Lucilius, who was given the nickname ‘Cedo alteram’ because of his habit of breaking a rod on the back of a legionary and then simply ordering another one. Lucilius and other unpopular centurions became the object of the soldiers’ wrath after the outbreak of the mutiny in 14 CE. The question arises as to whether the violent reaction of the soldiers was only the result of the behaviour of some centurions, or whether the system of granting promotions during the reign of Augustus was deeply flawed, enabling people with mental problems to have a military career. To find the answer, I have also used some elements of military psychology which, however, should not be overestimated due to the historical and cultural distance between the events of 14 CE and modern conflicts. In my opinion, the mutinies of the legions stationed in Pannonia and the Lower Germany are good illustrations of some of the serious problems affecting the Augustan army.